Implementasi Pertanian Cerdas Untuk Sistem Irigasi Tanaman Hortikultura Di Pesantren Karajaang Kapulauan Selayar - Sitti Nur Faridah; Muhammad Tahir Sapsal; Syahrial Sabaniah; Ahmad Munir; Mahmud Achmad; Suhardi; Iqbal; Husnul Mubarak (Departemen Teknologi Pertanian Universitas Hasanuddin, 2026)
This community service program aims to improve irrigation management efficiency and the productivity of horticultural crop cultivation through the implementation of smart farming technology at Karajaang Islamic Boarding School, Selayar Islands Regency. The primary challenges encountered by the partner included limited water availability, reliance on manual irrigation practices, and the absence of technological solutions to support the management of horticultural crop cultivation. The implemented solution consisted of installing a smart irrigation system equipped with soil moisture sensors and a microcontroller capable of automatically regulating irrigation based on the water requirements of horticultural crops. The implementation method included a needs assessment, system design and installation, as well as the demonstration and implementation of the technology. The results of the community service program demonstrated that the smart irrigation system significantly improved water use efficiency and enhanced the partner's knowledge and technical skills in the adoption and application of smart agricultural technologies. Furthermore, the participants demonstrated strong enthusiasm for operating the system and expressed their commitment to expanding its implementation to other horticultural cultivation areas. The implementation of this smart farming technology is expected to serve as a model for more efficient, sustainable, and climate-resilient horticultural crop management within the Islamic boarding school environment.